Chapter I lemmi nel settore dell'onomastica nel Glossarium illyricum (GKS 2071 - 4°) di Ch.F. Temler - Lazarevic Di Giacomo, Persida (Biblioteca di Studi Slavistici, 2018)
In the present paper the onomastic serial entries, specifically the names of nations and their respective substantival and/or adjectival forms, present in the "Glossarium illyricum" (Det Kongelige Bibliotek: GKS 2071 - 4°) of the Danish state secretary Christian Friedrich Temler (1717-1780) are analyzed. The results of the present study tend to demonstrate that the copy of the manuscript under consideration was not intended for publication.